Rhodococcus strains as a good biotool for neutralizing pharmaceutical pollutants and obtaining therapeutically valuable products: Through the past into the future - Ivshina, Irina; Bazhutin, Grigory; Tyumina, Elena (Frontiers in Microbiology, 2022)
Active pharmaceutical ingredients present a substantial risk when they reach the environment and drinking water sources. As a new type of dangerous pollutants with high chemical resistance and pronounced biological effects, they accumulate everywhere, often in significant concentrations (μg/L) in ecological environments, food chains, organs of farm animals and humans, and cause an intense response of the aquatic and soil microbiota. Rhodococcus spp. (Actinomycetes class), which occupy a dominant position in polluted ecosystems, stand out among other microorganisms with the greatest variety of degradable pollutants and participate in natural attenuation, are considered as active agents with high transforming and degrading impacts on pharmaceutical compounds. Many representatives of rhodococci are promising as unique sources of specific transforming enzymes, quorum quenching tools, natural products and novel antimicrobials, biosurfactants and nanostructures. The review presents the latest knowledge and current trends regarding the use of Rhodococcus spp. in the processes of pharmaceutical pollutants’ biodegradation, as well as in the field of biocatalysis and biotechnology for the production of targeted pharmaceutical products. The current literature sources presented in the review can be helpful in future research programs aimed at promoting Rhodococcus spp. as potential biodegraders and biotransformers to control pharmaceutical pollution of the environment.